ANALISIS SEMIOTIKA VISUAL ANIMASI UPIN & IPIN EPISODE “IKHLAS DARI HATI” - Yasa Aulia Putri, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
This study aimed to describe the visual animation Upin & Ipin with research restrictions on the episode  "Ikhlas  dari Hatit". The method used is qualitative descriptive method qualitative interpretative analysis. The  research focus is on visual analysis (color, gesture and characters), with a little review of the episode "Ikhlas  dari Hati". Data analysis using study semiotics Barthes to see two levels of meaning (denotative and  connotative), with supporters of the theory of semiotics Peirce to see signs (icon, index and symbol), and the theory of Saussure to see a marker (signified) and the sign (signifier) in several scenes and visual (color, gestures, characters) in the animation Upin & Ipin documented writer. The results of the research conducted,  it has concluded that animation of Upin & Ipin have a good visual communication strategies in the creation of characters, both of gesture, color and character. Thus developed a strong character. The message conveyed is well conceived and delivery simple, so it can follow the story line and easily understood.Keywords: Animation, Upin & Ipin, and Semiotics